ANALISIS KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR DALAM PEMBELAJARAN BAHASA INDONESIA - Rini Kristiantari, Maria Goreti; Chindytia; Delia Paramitha, Ni Putu; Dwi Kurniasih, Ni Kadek; Marsha Deamoza, Ni Putu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the speaking skills of elementary school students in Indonesian language learning. The problem addressed in this study was the low level of students’ speaking skills, particularly in terms of confidence, fluency, and vocabulary mastery. Many students tend to feel nervous, shy, and lack confidence when speaking in front of the class, which affects their ability to express ideas effectively. This research employed a qualitative descriptive approach involving 5 students and 1 teacher as research subjects. Data were collected through open-ended questionnaires using Google Forms and interviews to obtain in-depth information regarding students’ speaking skills. The results show that most students are still passive in speaking activities, have low confidence, and experience difficulties in organizing sentences and expressing ideas clearly. In addition, the learning process is still dominated by teacher-centered methods, which limit students’ opportunities to practice speaking. It is concluded that students’ speaking skills are still relatively low and need to be improved through the implementation of interactive and student-centered learning methods.